2000
DOI: 10.1152/ajpgi.2000.279.3.g613
|View full text |Cite
|
Sign up to set email alerts
|

PRL-1 PTPase expression is developmentally regulated with tissue-specific patterns in epithelial tissues

Abstract: The mechanisms controlling tyrosine phosphorylation of cellular proteins are important in the regulation of many cellular processes, including development and differentiation. Protein tyrosine phosphatases (PTPases) may be as important as protein tyrosine kinases (PTKs) in these processes. PRL-1 is a distinct PTPase originally identified as an immediate-early gene in liver regeneration whose expression is associated with growth in some tissues but with differentiation in others. We now demonstrate that the PRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…Interestingly, several tissues, which displayed a nuclear localization pattern for PRL-1 in mature tissue, showed evidence of some cytoplasmic expression during tissue development. It was also observed that the expression of PRL-1 became more consistently nuclear, as well as more cell type restricted, as development progressed (19). Based on these findings, it is an intriguing possibility that PRL proteins localized to the nucleus might function in terminal differentiation and/or that localization to membranes might allow PRLs to be involved in cell growth and metastasis.…”
Section: Biological Functions Of Prlsmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly, several tissues, which displayed a nuclear localization pattern for PRL-1 in mature tissue, showed evidence of some cytoplasmic expression during tissue development. It was also observed that the expression of PRL-1 became more consistently nuclear, as well as more cell type restricted, as development progressed (19). Based on these findings, it is an intriguing possibility that PRL proteins localized to the nucleus might function in terminal differentiation and/or that localization to membranes might allow PRLs to be involved in cell growth and metastasis.…”
Section: Biological Functions Of Prlsmentioning
confidence: 86%
“…PRL-1 and PRL-2 seem to be more ubiquitously expressed than PRL-3, as they are detected at low levels in various tissues (10,11,18). In addition to adult tissues, PRL-1 expression has also been examined during development, where it is expressed in several digestive epithelial tissues (19). PRL expression in normal tissues seems to correlate most often with terminal differentiation.…”
Section: Prl Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRL-1 was first identified as an immediate early gene expressed in regenerating liver and in serum-treated fibroblasts, and overexpression of PRL-1 in NIH 3T3 cells results in cell transformation, suggesting that the gene product plays a role in proliferation (23,30). Another role for PRL-1 has been proposed in the development and maintenance of differentiating epithelial tissues, as it is expressed in several developing tissues in fetal rat, and in the adult rat is found in terminally differentiated cells such as renal tubular epithelium, bronchiolar epithelium of the lung, and in villus but not crypt enterocytes of the intestine (31,32). Similarly, PRL-3 is specifically expressed in the differentiated epithelial cells of the villus but not in the proliferating crypt cells of the mouse small intestine (28).…”
mentioning
confidence: 99%
“…The mechanism of phosphorylation in tyrosine residues of cellular proteins is of paramount importance in development and differentiation process of cell. Pleiotropic regulatory locus 1 (PRL-1) are immediateearly gene in liver regeneration their presence is linked by development on some tissues but with differentiation in others [23]. Tyrosine phosphorylation has regulatory cellular functions on enzymatic activity, gene expression, cell cycle progression and motility [24,25].…”
Section: Gain/loss Of Function Of Ptp Towards Cancermentioning
confidence: 99%